PENGARUH PEMBELAJARAN IMLA TERHADAP KETERAMPILAN MENULIS BAHASA ARAB KELAS VII DI SMP AL FARISI (Program Studi Pendidikan Bahasa Arab, 2023)
Writing is the highest level of competency achievement among the other four competencies, therefore learning techniques are needed that are able to improve Arabic writing skills. Imla' is a learning technique to justify writing as well as improve writing that still needs improvement. This study aims to determine the process of learning to write sentences in Arabic by using the Imla' learning technique and to find out the existence of Arabic writing skills for class VII at al Farisi junior high school. This type of research is a pre-experimental design research type One-Group Pretest-Posttest Design with a quantitative approach. As for the research sample as many as 25 students from 94 populations. The sampling technique is purposive sampling, namely the technique of determining the sample with certain considerations. The data collection techniques used are: tests and documentation. The data analysis technique used is quantitative statistical analysis. The results of this study indicate that: (1) Imla' learning can help students improve their writing skills in Arabic. (2) By comparing the magnitude of t obtained in the calculations listed in the t-count value, it is known that t-count is greater than t-table where t-count = 2.93, while t-table = 1.708 (3) With the value of t-count t table , then the hypothesis can be accepted and this means that imla' learning has an effect on improving sentence writing skills in learning Arabic class VII at al Farisi junior high school